Filsafat Positivisme Dalam Kajian Implementasi Pantangan Pernikahan Bulan Suro (Muharam) Di Lenteng Sumenep Madura - Hafidz, Ahmad; Muhammadi, Hamas; Asmi, Moh; Akhmad, Hajarul Aswad; Rahmah, Ulfa Maulidiyah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This article describes a Javanese tradition in the form of a ban on marriage in the month of Suro which occurs in Lenteng Sumenep, in which the Javanese people, especially in Lenteng Timur Village, Lenteng sub-district, Sumenep Regency believe that for couples who marry in the month of Suro will get disaster, while in In view of the Islamic contex. marriage in the month of Suro is a month that is glorified by Allah swt and also this is the month in which the Prophet Muhammad taught his people to always do good, fast and increase alms. The data in this study were collected by means of interviews by examining various sources who discussed the taboo on marrying ulan Suro (Muharram). The results of this study reveal that the myth of prohibiting marriage in the month of Muharram (suro) is based on beliefs that have been passed down from generation to generation which until now people still believe that those who get married in the month of Muharram (suro) are called denial, even though Allah SWT has made all the days and months good. There are certain days that are very good, such as two feast days, Friday or the month of Ramadan. However, a good month is related to worship and nothing else.